Pengembangan Microsite Untuk Meningkatkan Kualitas Supervisi Akademik Pada Guru Paud Kecamatanan Ungaran Barat - Sri Janji; Widya Kusumaningsing; Rosalina BR.Ginting (Journal on Education, 2024)
The development of a microsite to improve the quality of academic supervision for early childhood education teachers is an application development using Information Communication Technology (ICT)-based microsite.s.id as a tool in carrying out academic supervision. The aim is to describe the implementation of factual academic supervision, develop microsite products, validate microsite products and analyze the validity of microsite products. This research method is Research and Development. Preliminary study with quantitative and qualitative approaches. Data collection techniques using interviews, questionnaires and observation. Test the validity of the data using source triangulation. The development stage involved experts and practitioners who refined the Delphi technique. The validity stage was carried out with a limited trial questionnaire, to determine the validity of the microsite development. Academic supervision carried out by school principals currently finds several challenges, namely: material guiding the quality of the learning process which is not yet understood by teachers, including; (1) learning planning (2) learning approach strategies, (3) learning content and (4) learning assessment to improve further learning. Based on the results of preliminary research, it is necessary to develop a microsite as a tool to carry out academic supervision. The conceptual model was then validated by experts and practitioners to produce a valid hypothetical model and then limited trials were carried out. The conclusions in this research are: (1) the factual model for implementing academic supervision still has weaknesses; (2) the microsite product developed is validated with a very good level of validity. It is hoped that the suggestions from this research will not only stop at validity, it can be tested on a limited scale and will continue with model trials on a wider scale.